The Effect of Eight-Week Swiss Ball Training on the Integration of Functional Movements and Balance of Teenage Badminton Players - Ali Asghar Saberian Amirkolaei; Ramin Balouchy; Rahman Sheikhhoseini (Shiraz University of Medical Sciences, 2019)
Background: Although injuries are an inevitable part of sports, exercise as a tool to prevent sports-related injuries and their consequences has caught the attention of many researchers in recent years. The present study aims to evaluate the effect of 8 weeks of Swiss ball training on the integration of functional movement of teenage badminton players and their balance. Methods: This is a semi-experimental research. A total of 29 teenage badminton players were selected and divided randomly into control (n=13) and experimental groups (n=16). The experimental group performed an eight-week-long period of Swiss ball training that was recommended by the Badminton World Federation before participating in the badminton exercise sessions (3 sessions per week). Before initiation, after the completion of the fourth and eighth week of trainings, both groups underwent Y balance and FMS tests. Results: Research findings indicated that eight weeks of Swiss ball training influenced FMS test (P≤0.001), lower limb Y balance test (P≤0.001), and upper limb Y balance test (P≤0.001) on the teenage badminton players. The post hoc testing identified a significant increase between weeks 4 and 8 in FMS tests (P≤0.001), lower limb Y balance test (P≤0.001) and upper limb Y balance test (P≤0.001). Conclusion: A period of 8 Weeks of Swiss ball training affects the integrity of functional movements and balance of teenage badminton players. Therefore, these protocols can be suggested for trainers and other related fields.